Variable Speed Control Moment Gyroscope in an Inverted Pendulum - Trentin, Joao F. S. [UNESP]; Silva, Samuel da [UNESP]; Schaub, Hanspeter (Asme, 2019)
The use of variable speed control moment gyroscope (VSCMG) is an effective way for attitude stabilization of aerospace devices. It is possible to control the oscillation and direction rate of change in rigid bodies in space due to the controlled change of angular momentum rate. Thus, this paper proposes an atypical pendulum configuration controlled by a VSCMG actuator. The idea of the VSCMG pendulum (VSCMGP) is to use both the angular momentum variation in amplitude and direction to implement the control. The controller is designed using Lyapunov theory to stabilize the pendulum in the inverted position. The results illustrate the control using a VSCMG in an inverted pendulum showing how the stabilization of an inverted pendulum is performed using two control actions. Also, the comparison of the proposed pendulum with a classical configuration is presented.
Keywords: reaction wheel; pendulum; nonlinear control; nonlinear dynamics; variable speed control moment gyroscope-VSCMG